Multidimensional apathy and executive dysfunction in amyotrophic lateral sclerosis. (September 2017) - Radakovic, Ratko; Stephenson, Laura; Newton, Judith; Crockford, Christopher; Swingler, Robert; Chandran, Siddharthan; Abrahams, Sharon
Abstract: Apathy and cognitive dysfunction are prominent symptoms of Amyotrophic lateral sclerosis (ALS). More specifically ALS patients show increased Initiation apathy-a lack of motivation for self-generation of thoughts as assessed by the Dimensional Apathy Scale. This study aimed to investigate the cognitive underpinnings of apathy subtypes in ALS. We hypothesized that increased Initiation apathy would be associated deficits on tests of intrinsic response generation, such as verbal fluency. We also explored the relationship of other apathy subtypes to cognitive processes, in particular emotional apathy with emotional and social cognition deficits and executive apathy with planning and goal management deficits. ALS patients, and their carers ( N = 30), and healthy matched controls, and their informants ( N = 29) were recruited. All participants completed self- and informant/carer-rated Dimensional Apathy Scale, to quantify apathy subtypes (Executive, Emotional and Initiation), along with standard apathy and depression measures. Patients and controls completed the Edinburgh Cognitive and behavioural ALS Screen, and a comprehensive neuropsychological battery including emotional recognition, social cognition, intrinsic response generation tasks (verbal fluency and random number generation) and a new ecologically valid, computerised measure of planning and goal management. The results demonstrated that increased Initiation apathy was the only significantly elevated subtype in ALS (self-rated p < .05, informant/carer-rated p < .01). Initiation apathy was found to be significantly associated with verbal fluency deficit, while Emotional apathy was significantly associated with emotional recognition deficits. No associations were found between apathy subtypes and depression or in controls. This is the first study to show specific associations between apathy subtypes (Emotional and Initiation) and executive and emotional cognitive dysfunction, indicating possible distinct underlying mechanisms to these demotivational symptoms.